2016
DOI: 10.1007/s12593-014-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome and Complications at 2.5 Years Following Volar Locking Plate Fixation of Distal Radius Fractures

Abstract: Distal radius fractures are increasingly treated by internal fixation, but there have been relatively few studies relating to functional outcome at 12 months or more. The aim of this study was to ascertain the patient reported function of the wrist at a minimum of 12 months following fixation of a distal radius fracture, the time taken to return to work, and the complication rate. We conducted a retrospective review of 187 consecutive patients treated by a specialist hand and wrist trauma team at a tertiary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…which compares favorably to several recent series of plate fixation. [26][27][28] Excluding the one outlier with VAS pain score of 8, our VAS pain scores ranged between 0 and 3, indicating a nil-to low-intensity of pain experienced by all patients except one, suggesting the procedure is quite well tolerated. Major complications (reoperation, hardware removal) were documented in four (18.1%) of the patients in this series, only two of which were symptomatic.…”
Section: Discussionmentioning
confidence: 92%
“…which compares favorably to several recent series of plate fixation. [26][27][28] Excluding the one outlier with VAS pain score of 8, our VAS pain scores ranged between 0 and 3, indicating a nil-to low-intensity of pain experienced by all patients except one, suggesting the procedure is quite well tolerated. Major complications (reoperation, hardware removal) were documented in four (18.1%) of the patients in this series, only two of which were symptomatic.…”
Section: Discussionmentioning
confidence: 92%
“…Based on 187 cases with an average follow-up period of 2.5 years, Macfarlane et al found that 8% of complications were caused by metacarpal plate screws, including three cases of tendon injury. This led them to recommended DVR for treatment of unstable distal radius fractures [17]. Two types of locking screws are used in the DVR system, threaded and unthreaded.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have investigated return to various activities after distal radius fracture. MacFarlane et al 7 found a median return to work time of 5 weeks after volar plating of distal radius fractures, and MacDermid et al 8 showed the mean time lost from work to be 9.2 weeks after sustaining a distal radius fracture. Jones et al 9 showed in a prospective study that 69.5% of patients undergoing volar plating of distal radius fractures would be deemed safe to drive at 18.4 days postoperatively, and an additional 17.4% of patients would be safe to drive at 31.3 days postoperatively.…”
Section: Discussionmentioning
confidence: 99%